1989
DOI: 10.2307/3899227
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Technology for Rangeland Management Applications

Abstract: ada Rena Paul has had over 30 years as student and professor working in the general area of Range Ecology and Management. He has initiated numerous studies concerned with range ecology, vegetation-soil relationships, range condition and trend, big game habitat management, brush encroachment, ecology of the pinyonjuniper woodland, mine waste reclamation, and remote sensing with emphasis on arid lands. Other qualifications include: commercial instrument rated pilot with over 3,000 hours, currently Associate Edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 4 publications
1
92
0
1
Order By: Relevance
“…While our results seem to support this claim, the choice of appropriate sample size will be critically important to achieve high accuracy. On the other hand, vegetation indices derived from several bands using different mathematical formulations may indicate quantitative and qualitative differences in the properties of vegetation because significant differences in reflectance and absorption of radiation exist between vegetation and other geographical characteristics of the landscape (Tueller, 1989). According to our analysis, normalized difference vegetation index (NDVI) appeared to be better than RVI and TNDVI for characterizing local-scale diversity and richness pattern in this particular desert landscape (Table 2).…”
Section: Relationship Between Tm Bands/derived Vegetation Indices Andmentioning
confidence: 79%
See 2 more Smart Citations
“…While our results seem to support this claim, the choice of appropriate sample size will be critically important to achieve high accuracy. On the other hand, vegetation indices derived from several bands using different mathematical formulations may indicate quantitative and qualitative differences in the properties of vegetation because significant differences in reflectance and absorption of radiation exist between vegetation and other geographical characteristics of the landscape (Tueller, 1989). According to our analysis, normalized difference vegetation index (NDVI) appeared to be better than RVI and TNDVI for characterizing local-scale diversity and richness pattern in this particular desert landscape (Table 2).…”
Section: Relationship Between Tm Bands/derived Vegetation Indices Andmentioning
confidence: 79%
“…According to our analysis, normalized difference vegetation index (NDVI) appeared to be better than RVI and TNDVI for characterizing local-scale diversity and richness pattern in this particular desert landscape (Table 2). Numerous studies have shown that NDVI is a sensitive indicator of green biomass (Tucker, 1979, Tueller, 1989). Out study suggested that, together with TM3 and TM7, NDVI was a good predictor of diversity and richness in the landscape of our study.…”
Section: Relationship Between Tm Bands/derived Vegetation Indices Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps, the most pressing extension is making the model's underlying ecological dynamics more realistic as well as more diverse. Here, the model can greatly benefit from a recent trend in rangeland ecology and pastoralism research: a growing body of research based on spatially as well as temporally fine-grained data on rangeland conditions, especially those derived from satellite imagery (Booth & Tueller, 2003;Egeru, 2014;Miller, 2015;Ruelland, Levavasseur, & Tribotté, 2010;Tueller, 1989). By fully employing these spatiotemporal data, the abstract and stylized aspects of the model can fruitfully be replaced with more data-driven dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation indices use radiance, surface reflectance or apparent reflectance values in the red (R) and near infrared (NIR) spectral bands (Gitelson, 2004;Tucker et al 2005;Zoran & Stefan 2006;Brown et al 2006;Angerer 2009). These indices are correlated with various vegetation parameters such as green biomass (Mutanga et al 2012;Ullah et al 2012), chlorophyll concentration (Clevers & Kooistra 2012), leaf area index (Mountrakis et al 2011;Yang et al 2012) and photosynthetic activity (Tueller 1989;Huete et al 2002;Li et al 2010). …”
Section: Spectral Vegetation Indices Utilize Unique Spectral Signaturmentioning
confidence: 99%